(untitled) (Research, Society and Development, 2025)
Infestation by Rhipicephalus (Boophilus) microplus, commonly known as the cattle tick, represents one of the main sanitary and economic challenges for Brazilian livestock. This hematophagous ectoparasite directly affects herd productivity, especially in extensive farming systems in tropical and subtropical climates. In addition to causing significant economic losses, the parasite is a vector of etiological agents of diseases such as Bovine Parasitic Sadness. This study aims to describe the damages caused by Rhipicephalus microplus infestations in cattle farming, as well as to explore solutions found in the literature, assisting producers in making decisions based on scientific evidence. A narrative literature review was conducted.